Fifteen-minute consultation: A structured approach to a child with primary spontaneous pneumothorax. Issue 5 (21st June 2021) - Buckley, Simon James; Adu, John; Whitaker, Donald; Gupta, Atul
Abstract : Primary spontaneous pneumothorax (PSP) is an uncommon presentation in children but may occur at any age and occurs in patients with no pre-existing lung disease. Management aims are to re-expand the collapsed lung, relieve pressure in the intrapleural space and avoid a tension pneumothorax. Correct management of PSP will avoid unnecessary intervention, reduce length of hospital stay and also reduce the risk of recurrence. There are no established guidelines for treating PSP in children and there is significant variation in management among centres and clinicians. This article provides a clear, evidence-based and structured approach to assessment and management of PSP in children and young people.